The multifaceted role of AIF-1 in metabolic dysregulation: bridging inflammation, insulin resistance, and obesity - Huang, Jie; Jiang, Fei; Chen, Yinling (Frontiers in Endocrinology, 2026)
Allograft inflammatory factor-1 (AIF-1), a cytokine secreted by activated monocytes, macrophages, and lymphocytes, has emerged as a critical regulator of pathological processes spanning renal diseases, rheumatoid arthritis, cancer, cardiovascular disorders, neurological pathologies, and transplant-related conditions. Population-based studies have associated sequence variants near the AIF-1 locus with obesity, though AIF-1’s potential pathophysiological involvement remains uninvestigated. Understanding its molecular characteristics, receptor interactions, and signaling pathways is essential for elucidating its biological functions. This review comprehensively examines AIF-1’s involvement in inflammatory and metabolic pathogenesis, particularly focusing on obesity and inflammation. Through systematic literature analysis, we consolidated current knowledge on AIF-1’s functions and analyzed studies exploring its roles in obesity, insulin resistance, and inflammation to clarify broader disease mechanisms. AIF-1 exerts pleiotropic effects on immune cells, insulin signaling, and adipocytes. Elevated AIF-1 levels correlate with inflammatory adipocytes and obesity, while reduced AIF-1 promotes weight loss through regulation of monoamine oxidase A and decreased leptin/resistin production. Deciphering AIF-1’s complex roles in inflammation and metabolic disorders offers critical insights for therapeutic development. Targeting AIF-1 or AIF1-like (AIF1L) may yield novel strategies to mitigate disease progression and enhance clinical management of obesity.